Diet-Induced Adipocyte Browning - Oskar Wojciech Wiśniewski; Aleksander Rajczewski; Agnieszka Szumigała; Magdalena Gibas-Dorna (Polish Journal of Food and Nutrition Sciences)
The adipocyte browning process is a phenomenon that consists in the molecular and morphological remodeling of preadipocytes or mature white adipocytes into multilocular beige fat cells expressing thermogenesis-associated genes. Adipocyte browning may occur physiologically, mainly upon cold or exercise stimulation. However, it can also be induced by exogenous compounds, such as drugs or dietary components. Since adipocyte browning is followed by increased energy expenditure, weight loss, and improved metabolic health, it emerges as a novel therapeutic target in the treatment of obesity and obesity-related diseases. In addition, it contributes to the lowering of adipose tissue and systemic inflammation, which are promoted in obese states. Thus, the role of adipocyte browning should be emphasized in the context of a dramatically increasing population of obese individuals. In this paper, we focus on dietary components and general dietary modifications, which may affect adipocyte browning by its stimulation or inhibition. We discuss browning properties of amino acids, carbohydrates, fatty acids, and retinoids, as well as present adipocyte browning potential of the wide range of non-nutrients, including glucosinolates, alkaloids, terpenes and terpenoids, flavonoids and other phenolic compounds. We also demonstrate the influence of edible plant extracts and food ingredient of animal origin on adipose tissue browning. Finally, we analyze browning effects of caloric restriction, intermittent fasting and various dietary macronutrient compositions, as well as the significance of microbiota in adipocyte browning process.